Numerical Analysis of Effective Parameters of Thermoelectric Module by Statistical Method - M. E. Kazemian; M. Khazali (Iranica Journal of Energy and Environment)
The thermoelectric module is advantageous due to its non generation of toxic waste and versatility across different scales.  As a renewable energy source and an alternative to fossil fuels, TEM is recognized as a promising candidate for energy extraction and thermal regulation. However, despite its potential as a renewable energy source, it seems that based on its limited efficiency and high costs necessitate an investigation into the key parameters affecting its performance. This involves the application of suitable methodologies to improve them in industries. In this study, the thermoelectric module has been numerically simulated, in order to investigate the influential parameters through statistical methods. The investigated parameters include the geometrical parameters of the rectangular leg pairs, such as their length, width, height, distance between them, quantity, as well as the temperature of the heated surface and the electric current input to the module. The cold side temperature and input voltage has been analyzed as responses by considering the affecting parameters. Analysis of variance (ANOVA) and central composite design have been employed to analyze responses. Moreover, in order to examine the impact of influential parameters on responses, a statistical sensitivity analysis was performed using the design of experiments and response surface methodology (RSM). The appropriate response functions were observed between factors and responses obtained from the statistical procedures. The study found that reducing the cross-section area of leg pairs from 4 mm² to 2 mm² and the hot surface temperature from 100°C to 50°C led to a 15% increase in input voltage. Furthermore, increasing the electric current from 2A to 4A and the height of leg pairs from 5 mm to 10 mm caused a 20% increase in input voltage and a 10% decrease in cold surface temperature.